Legal analysis on jurisdictional conflicts relating to waqf / Bailey Luigi Ubu…[et al.] - Ubu, Bailey Luigi; Muhammad Fauzi, Fathin Nadia; Ahmad Afandi, Nur Anis Farhah; Zulkifli, Nurnadmin (2012)
List II of the Ninth Schedule to the Federal Constitution provides that Islamic law is a state matter. Article 74(2) of the Federal Constitution empowers the legislature of a state to make laws for the whole or any part of the state in respect of any matter enumerated in the State List. Waqf is also included in one of the matters governed by states in Malaysia. According to List II of the Ninth Schedule, waqf falls under the jurisdiction of Syariah Court in Malaysia. On top of that, each state in Malaysia has enacted waqf 'laws, either in its own waqf enactment or in the Administration of Islamic Law Enactments. Although it is clearly provided in the legislation that disputes on waqf shall be heard in Syariah Courts, there are still several cases on waqf that are being heard and decided in Civil Courts. Follows from this, the people having interest in waqf under Islamic law are deprived of their rights. This paper will elaborate on the laws on waqf in Malaysia, examine the issues raised and several decided cases on waqf and discuss further on the jurisdiction of Syariah and Civil Courts in hearing disputes of waqf. Therefore, this paper is intended to provide an overview on the legislations and jurisdictions of courts concerning waqf in Malaysia.